Fatigue, depression, and physical impairment in multiple sclerosis - Azimian, Mojtaba (Iranian Neurological Association, 2014)
Background: Fatigue, depression, and physical impairment are common among multiple sclerosis (MS) patients. The aim of this study was to determine the relationship between depression, physical impairment, and fatigue in an Iranian MS cohort. Methods: Fifty consecutive relapsing-remitting MS patients and 50 age- and sex-matched healthy controls (HCs) were recruited from Sina Rehabilitation Clinic, Tehran, Iran. The depression substance of Hospital Anxiety and Depression Scale (HADS), Expended Disability Status Scale, and Fatigue Severity Scale questionnaires were used to assess depression, physical impairment, and fatigue, respectively. Results: This study included 38 (76%) females and 12 (24%) males in both patients and HC groups. The depression substance of the HADS in MS and HCs showed a mean value of 1.92 ± 0.80 and 1.17 ± 0.38, respectively (P < 0.001). Pearson’s correlation analyses showed that in the MS group depression was associated with fatigue (r = 0.54, P = 0.01), but not with physical impairment (r = 0.16, p = 0.01), while fatigue was associated with both depression (r = 0.54, P = 0.01) and physical impairment (r = 0.36, P = 0.01). Depression in HCs group was also associated with fatigue (r -0.64, P = 0.01). Conclusion: Fatigue is associated with both depression and physical impairment, and an intervention in one of these conditions might improve others.